Pengaruh Metode Pengasaman Menggunakan Cuka Alami terhadap Karakteristik Fisika dan Kimia Virgin Coconut Oil (VCO) Berdasarkan SNI - Sayakti, Putri Indah; Maharani, Nessa Astika; Anisa, Siti; Febriani, Reva Aura; Ramadhan, Hafiz; Pambudi, Didik Rio (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2025)
Virgin coconut oil is a modified result of coconut oil production. One method of making a VCO is by the acidification method using vinegar. In the process of making VCO, natural vinegar can produce good quality and environmentally friendly VCO because it comes from the fermentation process of organic materials, while commercial vinegar only contains acetic acid and gives a sharp taste and smell. This study aims to determine the effect of using commercial vinegar, kepok banana peel vinegar, honey pineapple peel vinegar, and rice vinegar made by the acidification method on the physical and chemical characteristics of VCO, as per SNI standards. Data were analyzed using ANOVA test. The results of physical and chemical quality tests of 5 samples obtained organoleptic test results, clear color, distinctive coconut odor, and distinctive taste of coconut oil. Specific gravity test 0.9178g/mL, 0.9166g/mL, 0.9175g/mL, 0.9175g/mL, and 0.9164g/mL. Water content test 0.1295%, 0.0486%, 0.0553%, 0.0511% and 0.1524%. Free fatty acid test 0.1390%, 0.1056%, 0.1144%, 0.1178, and 0.1822%. Peroxide number test 0.5457mgek/kg, 0.4933mgek/kg, 0.5670mgek/kg, 0.5113mgek/kg and 0.5889mgek/kg. So it can be concluded that the five samples produce physical and chemical characteristics in accordance with SNI. Based on the results of the ANOVA test, it is known that there is no significant effect on the value of specific gravity, water content, free fatty acid number and peroxide number with the use of commercial vinegar and natural vinegar compared to commercial VCO.